Analysis of Recent Research and Innovations in Vibration-Assisted Hybrid Machining Processes - Gupta, Kapil; Sarmah, Pallab; Pawanr, Shailendra (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Hybrid machining processes (HMP) have been developed to double the benefits of advanced or conventional machining processes by combining them. The challenges that occur in machining of intricate shapes and features, micromachining, and machining of very hard and soft materials can be overcome by HMPs. Assistance from external sources like vibrations, abrasives, and magnetic fields can facilitate material removal and enhance machining efficiency. This paper analyses some important recent research and innovations carried out in the domain of vibration-assisted HMPs and presents them to enrich the knowledge of scholars and researchers to establish the field further. The major focus of the article is to highlight the role of vibration assistance in facilitating both conventional and modern machining domains specifically covering electrochemical machining, electric discharge machining, turning, and their variants. Industry 4.0 and Sustainability-oriented innovations in advancing HMPs, involving leveraging digital technologies to enhance productivity while minimizing environmental impact, have also been featured